(untitled) (South East Asia Journal of Public Health, 2017)
In this paper, we present a patient who underwent an emergency exploratory laparotomy after Motor Vehicle Collison (MVC) leading to splenic injury, avascular necrosis of kidney and right upper extremity Colles’ fracture. Goal of the paper is to present a patient of polytrauma along with its treatment plan in terms of prioritizing the standard of care. We also discuss various radiographical findings along with gross surgical findings that were found intraoperatively. South East Asia Journal of Public Health Vol.7(1) 2017: 58-61